PSAK 24 : Gender Equality in Sustainable Development Goals - Diah Syifaul A'yuni; Rahma Sandhi Prahara (STEI Kanjeng Sepuh Gresik Jawa Timur, 2020)
Gender equality can be realized if there is fair treatment between women and men. Gender equality is 1 of 17 goals, namely the 5th goals contained in sustainable development goals that must be achieved in 2030 as a form of sustainable development. The Indonesian government sided with in making and passing various laws to eliminate inequality through gender bugeting which has the concept of reducing gender disparity in order to create gender responsive development and provide equal treatment and equal opportunities between men and women known as gender responsive budget (ARG). ARG is one of the effective instruments and strategies to reduce poverty, gender, social, economic, political gaps and between men and women in sustainable development for the sake of social justice for all people, especially Indonesia.